2003
DOI: 10.1242/jcs.00336
|View full text |Cite
|
Sign up to set email alerts
|

Central-pair-linked regulation of microtubule sliding by calcium in flagellar axonemes

Abstract: The movement of eukaryotic flagella and cilia is regulated by intracellular calcium. We have tested a model in which the central pair of microtubules mediate the effect of Ca2+ to modify the dynein activity. We used a novel microtubule sliding assay that allowed us to test the effect of Ca2+ in the presence or absence of the central-pair microtubules. When flagellar axonemes of sea-urchin sperm were exposed to ATP in the presence of elastase, they showed different types of sliding disintegration depending on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
118
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(133 citation statements)
references
References 39 publications
(48 reference statements)
12
118
0
3
Order By: Relevance
“…These results indicate that calcium regulation of flagellar motility in Chlamydomonas involves the regulation of dynein-driven microtubule sliding, that calmodulin and calmodulin-dependent kinase may mediate the calcium signal, and that the central apparatus and radial spokes are among the key components of the calcium signaling pathway [Smith, 2002a]. Similar microtubule sliding assays and reactivation studies using sea urchin sperm axonemes have also implicated the central apparatus in calcium-induced modulation of motility [Bannai et al, 2000;Nakano et al, 2003].…”
Section: Conserved Signaling Proteins Located In the Central Pair Andmentioning
confidence: 85%
See 1 more Smart Citation
“…These results indicate that calcium regulation of flagellar motility in Chlamydomonas involves the regulation of dynein-driven microtubule sliding, that calmodulin and calmodulin-dependent kinase may mediate the calcium signal, and that the central apparatus and radial spokes are among the key components of the calcium signaling pathway [Smith, 2002a]. Similar microtubule sliding assays and reactivation studies using sea urchin sperm axonemes have also implicated the central apparatus in calcium-induced modulation of motility [Bannai et al, 2000;Nakano et al, 2003].…”
Section: Conserved Signaling Proteins Located In the Central Pair Andmentioning
confidence: 85%
“…In these cell types, specific interactions of the radial spokes with the central apparatus may positively or negatively control dynein activity by a switching mechanism that does not involve central apparatus rotation. This notion is supported by the recent studies of isolated sea urchin sperm axonemes using a modified microtubule sliding assay [Yoshimura and Shingyoji, 1999;Nakano et al, 2003]. It is possible that rotation provides additional regulatory mechanisms that are primarily founded in the asymmetry of the central apparatus and that provide axonemes with versatility and an array of waveforms [for example, see Gray, 1928].…”
Section: Structural Analysis Of Central Pair and Radial Spoke Functionmentioning
confidence: 94%
“…We have observed that lf1, lf2, and lf4 flagellar waveforms show serious deviations from the WT waveform. This points the way to further work involving an in vitro microtubule-sliding assay with isolated axonemes so as to examine the possible role of the central pair in modulating dynein activity on specific doublet microtubules [38][39][40]. A closer look at mutant cell shapes is, therefore, warranted.…”
Section: Discussionmentioning
confidence: 99%
“…2 axonemes (Fig. 1b, c) and are involved in the activation or inactivation of dyneins on a specific doublet microtubule, resulting in the determination of the ciliary beating plane [14,15,164,165]. Mutations in the genes for RS/CP leading to ciliopathy include RS proteins (RSPH1, RSPH4A, and RSPH9) and those in the CP (HYDIN and SPAG17) ( Table 1).…”
Section: Deficiency In Other Axonemal Substructuresmentioning
confidence: 99%